Association of the non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio with non-alcoholic fatty liver disease and hepatic steatosis in United States adults: insights from NHANES 2017–2020 - Song, Zhen; Gu, Hai-Qi; Xu, Cheng (Frontiers in Nutrition, 2025)
ObjectiveThis study aimed to investigate the association between the non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) and NAFLD, as well as its relationship with hepatic steatosis and liver fibrosis, in a nationally representative sample of U.S. adults.MethodsThis cross-sectional study analyzed data from 3,529 participants from the National Health and Nutrition Examination Survey in 2017–2020. Multivariable logistic regression and subgroup analyses were used to assess the association between NHHR and NAFLD. Multivariate linear regression was employed to evaluate the relationship between NHHR and hepatic steatosis (controlled attenuation parameter) and liver fibrosis (liver stiffness measurement). Nonlinear relationships were explored through fitted smoothing curves and threshold effect analysis. Receiver operating curve (ROC) analysis was performed to compare the diagnostic performance of NHHR with body mass index (BMI), high-density lipoprotein cholesterol (HDL-C), and total cholesterol (TC).ResultsThe study included 3,529 participants (mean age: 51.34 years, 95% CI: 49.97, 52.72), with 53.53% male. NHHR showed a significant positive association with NAFLD after adjusting for confounders (OR: 1.33, 95% CI: 1.24, 1.42). Subgroup analysis indicated a stronger association in females and individuals with normal weight. A nonlinear relationship was identified, with a significant positive association below an inflection point of 4 (OR: 1.52, 95% CI: 1.38, 1.68). NHHR was positively associated with hepatic steatosis but not with liver fibrosis. For NAFLD diagnosis, NHHR achieved an area under the curve (AUC) of 0.66, outperforming TC (AUC = 0.51) but indicating lower accuracy than BMI (AUC = 0.77) and HDL-C (AUC = 0.68).ConclusionNHHR is positively associated with NAFLD and hepatic steatosis in U.S. population, highlighting the important role of lipid control in the prevention and clinical management of NAFLD.